Structural Connections for Small-Diameter Poles - Morgado, T. (2013)
In Portugal, given the large proportions of natural regeneration pine stands, a large amount of young trees must be removed from the forest, to assure the quality of mature trees and to decrease the risk of fire. With this problem in mind, a national study was launched to investigate the use of maritime pine small-diameter poles in structural applications. The study had two different tasks. The first task comprised the determination of mechanical properties and the establishment of visual and mechanical strength grading procedures and is already completed. The second task concerns the development of connections. This paper presents results within the second task. Three types of connections, regarding failure load and stiffness, were studied: connections using central plates; glued-in rods; and dowel nuts. The glued-in rods showed the highest mean failure load and, especially, stiffness. Indeed, the glued-in rods showed a mean stiffness around six times higher than the one obtained for the other studied connections. Additionally, the applicability of European Yield Model to estimate the failure load of these connections is also discussed. DOI: 10.1061/(ASCE)ST.1943-541X.0000752. © 2013 American Society of Civil Engineers.